2012
DOI: 10.2135/cropsci2011.08.0444
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Glutenin during Grain Development and Quality Expression in Winter Wheat in Response to Irrigation Levels

Abstract: wîges in the content and size distribution of glutenin were monitored using size-exclusionhigh performance liquid chromatography (SE-HPLG) during grain filling under field conditions in tv^o seasons. Effects of irrigation levels on the constituent polypeptides (high molecular weight and low molecular weight glutenin unit), polymerization index (the percentage of sodium dodecyl sulfate [SDS]-insoluble glutenins in total glutenins) of glutenin, glutenin macropolymer (GMP) particle size, dough mixing properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…This is consistent with previous studies that multiple heat and drought stresses modified the early dough stage and maturity, and shortened the kernel desiccation period (Zhang et al 2013). Jia et al (2012) also reported that the time of grain rapid dehydration was postponed with the increase of irrigation amounts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies that multiple heat and drought stresses modified the early dough stage and maturity, and shortened the kernel desiccation period (Zhang et al 2013). Jia et al (2012) also reported that the time of grain rapid dehydration was postponed with the increase of irrigation amounts.…”
Section: Discussionsupporting
confidence: 93%
“…It indicates that water availability may influence the accumulation of GMP and the size distribution of the glutenins through the modification of grain dehydration. This confirms the results of Jia et al (2012), who found that drought or excess water led to less and smaller GMP formed, indicating irrigation levels influenced both glutenin biosyn- thesis and glutenin particle formation. These data have shown that water availability and genotype are important factors that influence the formation of yield and flour quality, which is consistent with the results of Madani et al (2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Samples of 0-200 cm topsoil were collected in all experimental plots by using a soil auger at 20 cm increments, each sample was replicated three times. SWC on a weight basis was calculated using the oven drying method (Jia et al, 2012). Measurements were performed before sowing (Z00), 1 d before irrigation and 3 d after irrigation at both jointing (Z31) and anthesis (Z61) stages, and at maturity (Z90) stage.…”
Section: Experimental Designmentioning
confidence: 99%
“…Concurrently with soil respiration, gravimetric soil water content in the 0-5 cm and 5-10 cm depth was determined based on the method described by Jia et al (2012). Gravimetric water content at the two depth intervals was multiplied by soil bulk density to obtain the volumetric water content, which is expressed in cm 3 /cm 3 .…”
Section: Measurement and Calculationmentioning
confidence: 99%